Sex Differences in the Use of Statins in Community Practice: Patient and Provider Assessment of Lipid Management Registry. Issue 8 (August 2019) - Nanna, Michael G.; Wang, Tracy Y.; Xiang, Qun; Goldberg, Anne C.; Robinson, Jennifer G.; Roger, Veronique L.; Virani, Salim S.; Wilson, Peter W.F.; Louie, Michael J.; Koren, Andrew; Li, Zhuokai; Peterson, Eric D.; et al.
Abstract : Background: Female patients have historically received less aggressive lipid management than male patients. Contemporary care patterns and the potential causes for these differences are unknown. Methods and Results: Examining the Patient and Provider Assessment of Lipid Management Registry—a nationwide registry of outpatients with or at risk for atherosclerotic cardiovascular disease—we compared the use of statin therapy, guideline-recommended statin dosing, and reasons for undertreatment. We specifically analyzed sex differences in statin treatment and guideline-recommended statin dosing using multivariable logistic regression. Among 5693 participants (43% women) eligible for 2013 American College of Cardiology/American Heart Association Cholesterol Guideline–recommended statin treatment, women were less likely than men to be prescribed any statin therapy (67.0% versus 78.4%; P <0.001) or to receive a statin at the guideline-recommended intensity (36.7% versus 45.2%; P <0.001). Women were more likely to report having previously never been offered statin therapy (18.6% versus 13.5%; P <0.001), declined statin therapy (3.6% versus 2.0%; P <0.001), or discontinued their statin (10.9% versus 6.1%; P <0.001). Women were also less likely than men to believe statins were safe (47.9% versus 55.2%; P <0.001) or effective (68.0% versus 73.2%; P <0.001) and more likely to report discontinuing their statin because of a side effect (7.9% versus 3.6%; P <0.001). Sex differences in both overall and guideline-recommended intensity statin use persisted after adjustment for demographics, socioeconomic factors, clinical characteristics, patient beliefs, and provider characteristics (adjusted odds ratio, 0.70; 95% CI, 0.61–0.81; P <0.001; and odds ratio, 0.82; 95% CI, 0.73–0.92; P <0.01, respectively). Sex differences were consistent across primary and secondary prevention indications for statin treatment. Conclusions: Women eligible for statin therapy were less likely than men to be treated with any statin or guideline-recommended statin intensity. A combination of women being offered statin therapy less frequently, while declining and discontinuing treatment more frequently, accounted for these sex differences in statin use. Abstract : Supplemental Digital Content is available in the text.